Adaptive fuzzy prescribed performance control for MIMO nonlinear systems with unknown control direction and unknown dead-zone inputs. (January 2017) - Shi, Wuxi; Luo, Rui; Li, Baoquan
Abstract: In this study, an adaptive fuzzy prescribed performance control approach is developed for a class of uncertain multi-input and multi-output (MIMO) nonlinear systems with unknown control direction and unknown dead-zone inputs. The properties of symmetric matrix are exploited to design adaptive fuzzy prescribed performance controller, and a Nussbaum-type function is incorporated in the controller to estimate the unknown control direction. This method has two prominent advantages: it does not require the priori knowledge of control direction and only three parameters need to be updated on-line for this MIMO systems. It is proved that all the signals in the resulting closed-loop system are bounded and that the tracking errors converge to a small residual set with the prescribed performance bounds. The effectiveness of the proposed approach is validated by simulation results. Abstract : Highlights: An adaptive fuzzy prescribed performance control is developed for MIMO nonlinear systems with unknown control direction. The symmetric matrix decomposition technique is used to design the controller. Only one Nussbaum-type function is used to estimate the unknown control direction. Only three parameters need to be adjusted on-line, no matter how many subsystem there are.